Comparison HOR and AHP Methods in Risk Mitigation of Line Pipe Procurement - Kholid, Muhammad Arwan; Harito, Christian (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
OCTG (Oil Country Tubular Goods) is a type of pipe used for oil and gas exploration activities. To meet the demands for the fulfillment of Line Pipe material needs at PT Pertamina EP. The results of the analysis and identification of risk factors from 3 Subjet Matter Expert (SME) in Line Pipe material procurement activities. From 13 Process Activities, 16 Risk Events (Ei) and 35 Risk Agents (Aj) were obtained. In House of Risk (HOR) 1, the results of the calculation of the Aggregate Risk Potentials (ARPj) value of 35 Risk Agents (Aj), the highest Aggregate Risk Potentials (ARPj) with a value of 810. In House of Risk (HOR) 2, the results of the calculation of the Effectiveness to Difficulty ratio (ETDk) value of 4 Preventive Action (PAk), the highest Effectiveness to Difficulty ratio (ETDk) value with a value of 4860. In the Analytic Hierarchy Process (AHP), the results of the calculation of the Consistency Ratio value of 5 Criteria Weight the highest Criteria value with a percentage of 45.4% and the Consistency Ratio of 4 Alternatives the highest Alternative value with a percentage value of 44.06%. The best alternative solution in the selection of mitigation strategies for contract type selection is â€œTFC (Technical Framework Contract)â€ with the highest percentage and value. The TFC (Technical Framework Contract) contract type is in accordance with the PTK-007 Revision 5 Chapter IV Contract guidelines.